PENGARUH PEMBERIAN INFUSED WATER KURMA PADA IBU HAMIL TRIMESTER III DENGAN ANEMIA - Agi Yulia Ria Dini; Yosi Yusrotul Khasanah; Heny Puspasari; Siti Nurdiyana; Dian Susanti; Fitri Setiawati (Jurnal Medicare, 2025)
Anemia in pregnant women is a condition of low hemoglobin levels in pregnant women which is a common health problem and can affect both the mother and the fetus. One potential non-pharmacological method to overcome anemia is giving date infused water. Dates are rich in iron, vitamin B complex, and vitamin C which support the formation of hemoglobin and iron absorption. This study aims to analyze the effect of giving date infused water on hemoglobin levels in pregnant women. This study used a quasi-experimental design with a one-group pretest-posttest approach. The study population was all pregnant women in the third trimester with anemia at TPMB Mintarsih, S.SiT., Bd in the month of 33 people. The sampling technique was carried out using the total sampling technique. The results of the study showed that giving date palm infused water significantly increased hemoglobin levels in pregnant women with anemia in the third trimester. The Paired Samples Test statistical test produced a p value = 0.003 (p < 0.05), which indicates a significant effect of giving date palm infused water on increasing hemoglobin levels. This study recommends date infused water as a non-pharmacological intervention that can be used to support the health of pregnant women.